Thin films of silica nanoparticle doped nematic liquid crystal 7CB for electro-optic modulation - Marinov, Yordan G.; Hadjichristov, Georgi B.; Petrov, Alexander G.; Prasad, S. Krishna (Photonics Letters of Poland, 2015)
The amplitude-frequency electro-optic (EO) modulation by nanocomposite of room-temperature nematic liquid crystal heptylcyanobiphenyl (7CB) and 3 wt.% silica nanoparticles (SiNPs) of size 7nm, was studied. Thin (25μm) films of SiNPs-7CB soft gel exhibit an extended and flat second-harmonic EO modulation that can be of potential interest for EO applications. Full Text: PDF References M. Kreuzer, R. Eidenschink, Filled Nematics, in: Liquid Crystals in Complex Geomteries Formed by Polymer and Porous Networks. Eds: G.P. Crawford, S. Zumer, (London: Taylor and Francis 1996), Ch. 15, pp. 307?324. Y.A. Garbovskiy, A.V. Glushchenko: Liquid Crystalline Colloids of Nanoparticles: Preparation, Properties and Applications, in: Solid State Physics. 62, (Eds.) R.E. Camley, R.L. Stamps (New York, Academic Press, Elsevier 2011) pp. 1?4. A. Hourri, T.K. Bose, J. Thoen, "Effect of silica aerosil dispersions on the dielectric properties of a nematic liquid crystal", Phys. Rev. E 63, 051702 (2001). CrossRef F.M. Aliev, G.P. Sinha, M. Kreuzer, "Dynamics of Molecular and Collective Modes in Filled Nematic", Mol Cryst. Liq Cryst. 359, 217 (2001). CrossRef A.V. Zakharov, J. Thoen, "Effect of silica aerosils on the nematic to isotropic transition: A theoretical treatment", Phys. Rev. E 69, 011704 (2004). CrossRef C.V.Lobo, S.K. Prasad, C.V. Yelamaggad, "Experimental investigations on weakly polar liquid crystal-aerosil composites", J. Phys.: Condens. Matter 18, 767 (2006). CrossRef M.V. Kumar, S.K. Prasad, Y. Marinov, L. Todorova, A.G. Petrov, "Flexo-Dielectro-Optical Spectroscopy as a Method of Studying Nanostructured Nematic Liquid Crystals", Mol. Cryst. Liq. Cryst. 610, 51 (2015). CrossRef G.S. Iannacchione, J.T. Mang, T.P. Rieker, "Calorimetric and small angle x-ray scattering study of phase transitions in octylcyanobiphenyl-aerosil dispersions", Phys. Rev. E 58, 5966 (1998). CrossRef C.W. Garland, R. Bandyopadhyay, D. Liang, R.H. Colby, J.L. Harden, R.L. Leheny, "Enhanced Elasticity and Soft Glassy Rheology of a Smectic in a Random Porous Environment", Phys. Rev. Lett. 94, 107801 (2005). CrossRef V. Jayalakshmi, G.G. Nair, S.K. Prasad, "Effect of aerosil dispersions on the photoinduced nematic?isotropic transition", J. Phys.: Condens. Matter 19, 226213 (2007). CrossRef R.L. Leheny, S. Park, R.J. Birgeneau, J.L. Gallani, C.W. Garland, G.S. Iannacchione, "Smectic ordering in liquid-crystal?aerosil dispersions.I.X-ray scattering", Phys. Rev. E 67, 011708 (2003). CrossRef G.S. Iannacchione, S. Park, C.W. Garland, R.J. Birgeneau, R.L. Leheny, "Smectic ordering in liquid-crystal?aerosil dispersions. II. Scaling analysis", Phys. Rev. E 67, 011709 (2003). CrossRef A. Roshi, G.S. Iannacchione, P.S. Clegg, R.J. Birgeneau, "Evolution of the isotropic-to-nematic phase transition in octyloxycyanobiphenyl+aerosil dispersions", Phys. Rev. E 69, 031703 (2004). CrossRef G.S. Iannacchione, "Review of liquid-crystal phase transitions with quenched random disorder", Fluid Phase Equlibria 222-223, 177 (2004). CrossRef S. Lee, C. Park, "Agglomeration of Silica Nanoparticles in Filled Nematic Liquid Crystals", Mol. Cryst. Liq. Cryst. 333, 123 (1999). CrossRef T. Bellini, M. Buscaglia, C. Chiccoli, F. Mantegazza, P. Pasini, C. Zannoni, "Nematics with Quenched Disorder: What Is Left when Long Range Order Is Disrupted?", Phys. Rev. Lett. 85, 1008 (2000). CrossRef M. Caggioni, A. Roshi, S. Barjami, F. Mantegazza, G.S. Iannacchione, T. Bellini, "Isotropic to Nematic Transition of Aerosil-Disordered Liquid Crystals", Phys. Rev. Lett. 93, 127801 (2004). CrossRef S.A. Pikin, Strukturnie Prevrashcheniya v Zhidkih Kristallah (in Russian) (Moscow, Nauka 1981) p. 201.